The genus Bradysia Winnertz (Diptera, Sciaridae) in New Caledonia, with the description of thirteen new species - Vilkamaa, Pekka; Hippa, Heikki; Mohrig, Werner (Zootaxa, 2012)
The following species of the genus Bradysia Winnertz, 1867 are recognized from New Caledonia, all newly described: Bradysia aequispina sp. n., B. centidens sp. n., B. clavistylis sp. n., B. filigera sp. n., B. gemellata sp. n., B. gibbosa sp. n., B. melina sp. n., B. nudilobata sp. n., B. paucidens sp. n., B. planistylata sp. n., B. seticornis sp. n., B. spissa sp. n. and B. stricta sp. n. A key to the species is given.